Sketches of Frank Gehry - Pollack, Sydney ([s.l.] SP Architecture Productions, 2007)
A documentary on the grandeur of Gehry's architecture from his earliest building, a hay barn in California, to what are now recognized to be some of the great buildings of the modern era, including the Guggenheim Museum Bilbao and the Walt Disney Concert Hall in Los Angeles. Explores Gehry's process of turning his abstract drawings, first into tangible, three-dimensinal models, often made simply of cardboard and scotch tape then into finished buildings of titanium and glass, concrete and steel, wood and stone. Pollack's ability to pierce the skin of architectural theory allows him to draw deep insights into the life of this extraordinary architect and his singualr architectural process.
Keywords: Gehry, Frank